ChemInform Abstract: Synthesis of 5, 6‐Dihydropyran‐2‐one Derivatives under Coupled Ultrasonication and Phase Transfer Catalyzed in situ Generated Ketene with Chalcones. Issue 19 (May 2015) - Gupta, Ragini; Jain, Anshu; Varshney, Bindu
Abstract: Ultrasound‐mediated hetero Diels—Alder reaction of chalcones (II) with ketenes, generated in situ from acetyl chlorides (I) under phase‐transfer catalysis conditions, results in the efficient formation of dihydropyranones (III).